IMPLEMENTATION OF THE MODEL FOR MASTERS PREPARATION TO EDUCATIONAL AND SCIENTIFIC ACTIVITY IN THE CONDITIONS OF MASSIVE OPEN ONLINE COURSES - Oleksandr M. Samoylenko; Ilona V. Batsurovs’ka; Oleksii O. Samoylenko; Nataliia A. Dotsenko (Інформаційні технології і засоби навчання, 2018)
The article presents the results of experimental work. It is suggested to state and analyze the results of model implementation for masters preparation to educational and scientific activity in the conditions of massive open online courses. There are indicated specialties of the future masters that took part in the experimental work, considered the list of adapted massive open online courses, in which the basis of the technologies of teaching is laid, offered the author's model. There are presented computational tables of the empirical value χ2 of the motivational, cognitive-content, reproductive and operative and productive and creative component at the beginning and at the end of the experiment in control and experimental groups, the graphic correlation on the coordinate axis of the critical and empirical values of the indicated components and the graphs of the results of the assessment of the readiness of masters educational and scientific activity in the conditions of massive open online courses at the beginning and at the end of the expedition rhythm in relative frequencies.